A record of ancient cataclysm in modern sand: Shock microstructures in detrital minerals from the Vaal river, Vredefort Dome, South Africa - Cavosie, Aaron; Quintero, R.; Radovan, H.; Moser, D. (Geological Society of America, 2010)
The record of terrestrial meteorite impacts is fragmentary because most impact structures and ejecta are removed by erosion or buried. Discovery of the missing impact record from Hadean to present may be advanced through identification of residual shocked detritus. To evaluate which shocked minerals survive erosion and sedimentary transport, we investigated modern sands from the Vaal River in South Africa, where it crosses the 2.02 Ga Vredefort Dome, the largest terrestrial impact structure known to date. Shocked minerals were identified in all sediment samples, including from the Vaal channel and tributaries within the structure. In transmitted light, detrital quartz preserves discontinuous decorated planar features previously identified as Brazil twins, which are readily visible as bright, continuous features in cathodoluminescence images. Detrital zircons preserve five orientations of planar fractures (PFs), which can produce dramatically offset growth zoning and apparent rotation of subgrains. Other zircons contain filled fractures that may represent a new shock microstructure. Detrital monazite preserves four orientations of PFs, and many grains contain oscillatory-zoned shocked zircon inclusions, which thus represent shocked inclusions within shocked accessory grains. Zircon and monazite with granular texture were also identified. This study is proof of the concept that shocked minerals can be identified in sediments up to 2 billion years after an impact event, and it demonstrates their potential for preserving evidence of ancient impacts. The recognition of a new geological repository for impact evidence provides a means for identifying distal shocked detritus from eroded structures of any age, and may be particularly relevant to early Earth studies. © 2010 Geological Society of America.